Recurrent bleeding in a healthy child-A case of lupus anticoagulant-hypoprothrombinemia syndrome: A case report with review of literature - Sudesh Kumar; Piyali Bhattacharya; Shreemant Gautam; Nandita Chattopadhyay (Wolters Kluwer Medknow Publications, 2023)
Background: Although lupus anticoagulant (LA) is known to be associated with an increased risk of thrombosis and obstetric complications, typically seen in antiphospholipid syndrome, the presentation of LA-hypoprothrombinemia syndrome (LA-HPS) is different with bleeding manifestations more common than thrombosis. We report such a rare disorder in an otherwise healthy boy, who presented with subcutaneous bleeding and was treated successfully. Clinical Description: A 9-year-old boy presented with acute-onset swelling in the popliteal fossa region of the left leg and left great toe. History of fever, trauma, drug intake, joint pain, epistaxis, or melena was absent. Since 6 months of age, he had recurrent episodes of multiple, painful joint, and soft-tissue swellings and ecchymotic patches which subsided spontaneously. Examination showed a tense, shiny bluish patch over the left popliteal fossa and a swollen tender left great toe, without any lymphadenopathy, hepatosplenomegaly, or arthritis. Management and Outcome: Routine hemogram and liver function tests were normal. Furthermore, antinuclear antibody and rheumatoid factor were within normal limits. Coagulation studies showed prolonged prothrombin time (PT) and activated partial thromboplastin time (APTT), though bleeding and coagulation times were normal. Administration of Vitamin K and fresh frozen plasma (FFP) showed no improvement. Further investigations revealed normal values of von Willebrand Factor collagen binding, Factor VIII, Factor XIII, and fibrinogen, whereas prothrombin levels were reduced. The partial thromboplastin time-LA specific was high (170.10), suggesting a diagnosis of LA-HPS. The symptoms responded to prednisolone therapy, and there was complete recovery. Conclusion: A recurrent bleeding disorder with increased PT/APTT, not responding clinically to FFP transfusion, should raise suspicion of LA-HPS and appropriate tests need to be done. The prognosis of this disorder is good with corticosteroid therapy.